THE IMPLEMENTATION OF FLIPPED CLASSROOM BY USING SCHOOLOGY IN SPEAKING II CLASS OF ENGLISH EDUCATION STUDY PROGRAM OF TEACHER TRAINING AND EDUCATION FACULTY OF BANDAR LAMPUNG UNIVERSITY - David Ginola; Dameria Magdalena Sidabalok (International Conference on Education and Language (ICEL), 2016)
This research aimed at implementing flipped classroom method by using Schoology in speaking class. The participants of this research are the second semester of English Education Study Program in UBL who took speaking II class. The instruments are the observation and questionnaire. So the data of the research are gathered by doing the observation and giving questionnaire about opinion about both session (online and offline) which are made based on the observation data to the students. Result of the research showed that the students became more active, and also their achievement is better after experiencing in both sessions.